Kajian Dampak Ketidaknormalan Meter Elektronik Pada Sistem Automatic Meter Reading Pada Pelanggan Tegangan Rendah - Samsurizal, Samsurizal; Siagian, Faber Agustinus G; Makkulau, Andi (Universitas Halu Oleo, 2021)
PT. PLN (Persero) as an lsitrik energy provider has the task of checking and measuring the use of electricity used by customers. In this case of course requires technology to be able to read how much electrical energy is used, one of the technologies used is Automatic Meter Reading (AMR).Â Â The use of Automatic Meter Reading (AMR) system includes monitoring, recording the stand meter then the data can be displayed in the form of a report with data software used management. Electronic meters using AMR systems can be used as a detection tool against irregularities from troubled customers. The readings obtained from AMR are known to the customer's usage, moments before the maintenance error and after. So that it can accurately detect customers who occur maintenance errors and customers and PLN both know the amount of uncollectible kWh, so far the nursing has been impaired by maintenance errors from the beginning of the tide. Based on existing data AMR should not be worth kWh value, but with the error of maintenance in phase S kWh measurable import that will be calculated to obtain a follow-up bill. The result obtained is true there is an inverted phase, it is shown in the fasor diagram where the angle of phase S which was originally 168.30 to 14.40. So that in the stand meter becomes minus the impact due to the mistake of maintenance obtained follow-up bill is 41538.8 kWh equivalent to Rp. 60.949.050,- after calculation. It shows the impact that occurs due to the mismanagement of the follow-up bill that must be borne